Możliwości wykorzystania procesów sukcesyjnych w przebudowie drzewostanów na gruntach porolnych na przykładzie Nadleśnictwa Wielbark - Krawczyk, Robert (Leśne Prace Badawcze, 2021)
In the Wielbark Forest District, and many other forest districts in Poland, disturbances caused by annosum root rot Heterobasidion annosum (Fr.) Bref. have been observed regularly in timber stands cultivated on post-agricultural land. Natural regeneration in the resulting gaps is dominated by birches, but also other tree and shrub species occur. A better understanding of those natural successional processes is required in order to possibly include them in management practices, i.e., to employ them as an aid in stand conversion or improvement. This goal formed the foundation for this study, which was carried out under the assumption that the natural renewal of trees owing to annosum root rot would satisfy the requirements for silvicultural practices. The work was carried out in a pine stand sequence, aged from 1 to 100 years, representing two habitat types, fresh coniferous forest (Bśw) and fresh mixed coniferous forest (BMśw), grown on post-agricultural land with a total area of 15 757.31 ha. A 100×100 m square grid was established within which 125 circular sampling fields were selected randomly. Both, the existing timber trees and natural regrowth were measured, including an estimation of H. annosum sporocarps to show whether root rot infection had taken place. A detailed analysis of changes in the stocking index revealed that the most damaged tree stands belong to the third age group in both habitats. However, the changes observed in stands from the Bśw habitat were smaller and occurred with a delay compared with those from the BMśw habitat. In conclusion, in response to a disturbance caused by annosum root rot, natural regrowth appeared, involving 4 and 8 tree species respectively in the Bśw and BMśw habitats, but for both habitats, the regrowth was mostly comprised of pine and birch. Therefore, the results from this study clearly indicate that spontaneous regenerative processes would be of use if they were to be included in silvicultural practices.